Global assessment of morbidity and mortality pattern of CoVID-19: Descriptive statistics overview - Engy Refaat Rashed (Emergency Department of Hospital San Pedro (Logroño, Spain), 2020)
Introduction: Coronavirus disease 2019 is the recent most devastating global outbreak that influenced humanity in the new millennium since decades from the last devastating pandemic. Despite being of low mortality rates - if compared with the previous epidemics in human history - the progressively spreading epidemic does not impact health and life but also has changed man's lifestyle, economy, politics and many other undisputed admitted daily routines. Methods: The present case provides statistical analysis with a unique perspective using statistical process control (SPC) methodologies in a fast, simple and efficient way to study disease dissemination in terms of morbidities and mortalities globally. Results: Countries and territories with low population count were subjected relatively to a higher count of morbidities and mortalities than those of higher census count. Accordingly, the associate cases and death rates would be greater with a lower population number, suggesting that other factors should be involved in the outbreak hazard rather than the population number. Countries were arranged dissentingly by the residential census for illustration. The main contributing countries that showed collectively about 60% of the total CoVID-19 cases and deaths were arranged in descending order like the following: for cases, USA, Italy, Spain, China and Germany and for deaths, Italy, Spain, USA and France. A cubic relationship exists between the emerging number of cases and daily death records. CUSUM charts showed that the daily variations of the epidemic disease records have been rising and became out-of-control statistically on 17 and 19 March 2020. Conclusion: SARS-CoV-2 is still showing progressive dissemination patterns globally with variable impact between different countries or territories.